Relationship Between Placenta Accreta Index Score and Management in Placenta Accreta Patients in RSUP Dr. M. Djamil Padang - Azhari, Nabilah; Defrin, Defrin; Nurhayati, Nurhayati (Andalas Obstetrics And Gynecology Journal, 2025)
Introduction : Placenta acreta index is a scoring system using ultrasound parameters used to diagnose placenta accreta. Parameters included are the number of previous caesarean section, location of the placenta, grading of lacunae, presence of bridging blood vessels, thickness of the myometrium. The management of placenta accreta is conservative and definitive management, where the definitive management performed is hysterectomy. The purpose of this study was to determine the relationship between PAI score and placenta accreta management in patients with placenta accreta at Dr. M. Djamil Hospital Padang. Method : This type of research was observational analytic with cross sectional research design. This study was conducted in the medical record section uses a total sampling technique of 184 patients. Data analysis used univariate analysis, bivariate with Chi square test. Result : The results of this study showed that 67.9% of patients with PAI≥4 scores, 56.5% of patients who underwent hysterectomy, and after the statistical test obtained a p value <0.001, then H0 was rejected, meaning that there was a relationship between placenta accreta index scores and placenta accreta management. Conclusion : It is conclude from the results of this study there is a significant relationship between PAI score and placenta accreta management (P<0.05) in placenta accreta patients. Keywords: Hysterectomy, placenta accreta, PAI score